2021
DOI: 10.3390/antiox10101518
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evidence for the Interplay between Oxidative Stress and RIP1-Dependent Cell Death in Neurodegeneration: State of the Art and Possible Therapeutic Implications

Abstract: Neurodegenerative diseases are the most frequent chronic, age-associated neurological pathologies having a major impact on the patient’s quality of life. Despite a heavy medical, social and economic burden they pose, no causative treatment is available for these diseases. Among the important pathogenic factors contributing to neuronal loss during neurodegeneration is elevated oxidative stress resulting from a disturbed balance between endogenous prooxidant and antioxidant systems. For many years, it was though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 149 publications
(228 reference statements)
0
8
0
Order By: Relevance
“…GLU and DA are essential neurotransmitters, but in excess in the extracellular environment, they may induce neuronal damage and degeneration, which is involved in the pathophysiology of schizophrenia. Different mechanisms are involved in such neurotoxicity, including oxidative stress, oxytosis, mitochondrial damage and cellular apoptosis [13,43,45,46], which could be affected in different ways by CLZ and JNJ treatments. JNJ showed a potential neuroprotective effect in vitro, as it reduced the activation of caspase 3 induced by DA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLU and DA are essential neurotransmitters, but in excess in the extracellular environment, they may induce neuronal damage and degeneration, which is involved in the pathophysiology of schizophrenia. Different mechanisms are involved in such neurotoxicity, including oxidative stress, oxytosis, mitochondrial damage and cellular apoptosis [13,43,45,46], which could be affected in different ways by CLZ and JNJ treatments. JNJ showed a potential neuroprotective effect in vitro, as it reduced the activation of caspase 3 induced by DA.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of GLU-induced cell damage in neuronal-like cell models may differ from those found in primary neuronal cell cultures. It has been reported that cell exposure to high concentrations of GLU evokes oxidative stress and oxytosis, which could engage various cell death programs such as caspase 3 and/or caspase 3-independent apoptosis or necroptosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Following phosphorylation, MLKL oligomerizes and a small part of these oligomers moves towards the cell membrane where they mediate their effect in two different ways, either directly by facilitating the formation of pores across the cell membrane mediated through binding to membrane phospholipids like phosphatidylinositol phosphate and cardiolipin or indirectly by increasing influx of ions (Na + , K + , Mg 2+ , and Ca 2+ ) through recruitment of cation channels and Ca 2+ channels, the transient receptor potential melastatin related 7 (TRPM7), thereby increasing osmotic pressure and eventually leading to cell rupture ( vanden Berghe et al, 2016 ; Seifert and Miller, 2017 ; Dhuriya and Sharma, 2018 ; Li L. et al, 2021 ). Meanwhile, another part of MLKL oligomers translocates into the membranes of various organelles e.g., nucleus, mitochondria, endoplasmic reticulum (ER), and lysosomes, causing their damage via necroptotic cell death ( Li L. et al, 2021 ; Jantas and Lasoń, 2021 ).…”
Section: Necroptosis In Cp-induced Acute Kidney Injury (Aki)mentioning
confidence: 99%
“…Neurodegeneration is characterized by the excessive loss of neurons, which is triggered by a wide variety of environmental, physiological, and genetic factors [ 31 ]. Oxidative stress (OS) has been identified as one of the main pathological factors promoting neuronal degradation [ 31 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Excessive exposure to reactive oxygen species (ROS) compromises the integrity of biomolecules (such as lipids, DNA and proteins), ultimately causing necrosis and cell death [ 58 ].…”
Section: Introductionmentioning
confidence: 99%